Computational Mapping of Dirhodium(II) Catalysts. Issue 7 (12th January 2021) - Green, Adam I.; Tinworth, Christopher P.; Warriner, Stuart; Nelson, Adam; Fey, Natalie
Abstract: The chemistry of dirhodium(II) catalysts is highly diverse, and can enable the synthesis of many different molecular classes. A tool to aid in catalyst selection, independent of mechanism and reactivity, would therefore be highly desirable. Here, we describe the development of a database for dirhodium(II) catalysts that is based on the principal component analysis of DFT‐calculated parameters capturing their steric and electronic properties. This database maps the relevant catalyst space, and may facilitate exploration of the reactivity landscape for any process catalysed by dirhodium(II) complexes. We have shown that one of the principal components of these catalysts correlates with the outcome (e.g. yield, selectivity) of a transformation used in a molecular discovery project. Furthermore, we envisage that this approach will assist the selection of more effective catalyst screening sets, and, hence, the data‐led optimisation of a wide range of rhodium‐catalysed transformations. Abstract : A knowledge base for dirhodium(II) catalysts, capturing their stereoelectronic properties, maps the relevant catalyst space and supports catalyst selection.